The Role of Numbered Heads Together in Developing 21st-Century Skills in Civic Education: Evidence from Indonesian Junior High School Students - Febriza Laila Husna; Maria Montessori (AL-ISHLAH: Jurnal Pendidikan, 2025)
21st-century learning emphasizes the development of collaboration and communication skills, especially in Civic Education (PPKn). This study examines the impact of the Numbered Heads Together (NHT) cooperative learning model on enhancing these skills among Grade VIII students at SMP Negeri 8 Sungai Penuh. A quantitative approach with a quasi-experimental, posttest-only control group design was employed. A total of 64 students were selected through purposive sampling and divided evenly into an experimental group (NHT model) and a control group (conventional discussion). Collaboration skills were assessed using observation sheets, while communication skills were evaluated through a structured group presentation rubric. Independent sample t-tests were used for data analysis. The experimental group demonstrated significantly higher collaboration (82.3%) compared to the control group (76.59%). The t-test results confirmed a statistically significant difference in collaboration skills (t = 2.352, p = 0.022). Similarly, communication skills in the experimental group were significantly improved (t = 2.597, p = 0.001), indicating the effectiveness of the NHT model in fostering interpersonal competencies. These findings support constructivist and social learning theories, which emphasize active participation and peer interaction. The NHT model facilitates a collaborative learning environment that promotes student engagement and improves communication fluency and group cooperation. The NHT model is effective in improving students' collaboration and communication skills in PPKn learning. Its integration into classroom practice is recommended to support the development of essential 21st-century skills in secondary education.